CREATION: técnica de criatividade para geração de ideias de novos produtos - Fernandes, Marcela Squires Galvão (2014)
Creativity is a skill found in all individuals and one of the strategies used to intensify it is through the application of creativity techniques. In order to propose a new technique for generating new crafts product ideas, this dissertation, which is part of a research project of the Federal University of Rio Grande do Norte, through action research, intervened in three state communities artisans - Lajes Pintada, Massaranduba and Vera Cruz - to develop the artisans creative potential. Based on the techniques studied in the literature, we selected three techniques for interventions, composing two dynamics - one to improve features and functionalities of existing products, with the technique of SCAMPER; and the other to generate ideas for creating new products, with techniques Listing and Random Words / Figures. These latter techniques were not satisfactory in its objective by presenting constraints, not covered in the description, for the participant group. Thus, it was necessary to propose a new technique for the same purpose, the technique CREATION Clarify technique, Realized creativity, Explain, Apply for word, Think fast, Interpret, Organize ideas, Now evaluate, composed of twelve steps. To use the new technique requires that it be used by a dynamic that takes into account three phases: Planning, Application and Analysis. In the new technique application were generated around 30 ideas, regarded as new, in six sessions, from test pilot to interventions in artisans communities